1992
DOI: 10.1002/bdd.2510130505
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ibuprofen enantiomers after single and repeated doses in man

Abstract: The pharmacokinetic parameters of ibuprofen enantiomers after a single 600 mg dose and repeated 3 x 400 mg doses of Nurofen were determined in 12 healthy volunteers. Terminal half-lives were similar for both enantiomers, but plasma levels of S-ibuprofen were higher than those of R-ibuprofen, due to the chiral inversion and differences in distribution and metabolism. Comparison of maximal concentrations and areas under the concentration vs time curves between the first and last doses for each enantiomer indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The determined plasma concentrations of R ‐ and S ‐ibuprofen after oral administration were in agreement with previously published data 67 , 68 , 69 , 70 . The R/S ratios in plasma and the relative amounts of ibuprofen and metabolites in urine were similar after both routes of administration.…”
Section: Discussionsupporting
confidence: 90%
“…The determined plasma concentrations of R ‐ and S ‐ibuprofen after oral administration were in agreement with previously published data 67 , 68 , 69 , 70 . The R/S ratios in plasma and the relative amounts of ibuprofen and metabolites in urine were similar after both routes of administration.…”
Section: Discussionsupporting
confidence: 90%
“…Significantly ( P < 0.05) higher AUC values for S(+)‐ibuprofen were observed compared with R(−)‐ibuprofen after crop bolus and proventriculus administration as shown in Table 2. As the differences in AUC values are already measured in the 10 min after crop and proventriculus administration, it is unlikely that they originated from the occurrence of a chiral inversion from R(−)‐ibuprofen into S(+)‐ibuprofen as described for ibuprofen in humans (Oliary et al ., 1992; Cheng et al ., 1994) and in dogs (Ahn et al ., 1991). It could be hypothetized that both enantiomers are absorbed in a different way because of stereospecific absorption mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have suggested that chirality may be one of the main factors that account for inter-individual variability (1), others that it may be responsible for toxic effects (1,2). It is also generally thought that bioinversion of an enantiomer occurs, and that, in the profen group, this bioinversion is one-way, yielding the active enantiomer S(+) (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%